A flexible pressure sensor based on an MXene–textile network structure. Issue 4 (9th January 2019) - Li, Tongkuai; Chen, Longlong; Yang, Xiang; Chen, Xin; Zhang, Zhihan; Zhao, Tingting; Li, Xifeng; Zhang, Jianhua
Abstract : High-performance pressure sensors have attracted considerable attention recently due to their promising applications in touch displays, wearable electronics, human–machine interfaces, and real-time physiological signal perception. Abstract : High-performance pressure sensors have attracted considerable attention recently due to their promising applications in touch displays, wearable electronics, human–machine interfaces, and real-time physiological signal perception. However, the "functionality" of a sensor is generally incompatible with "simple" fabrication strategies. Therefore, strategies that are less equipment-intensive and less expensive are required for enhancing the sensor performance. Here, we propose a flexible piezoresistive pressure sensor based on MXene–textile prepared by a facile dip-coating process. Benefiting from the excellent electrical properties of MXene and the abundant wavy surface of cotton textile, this pressure sensor exhibits high sensitivity (12.095 kPa −1 for the range 29–40 kPa and 3.844 kPa −1 for the range less than 29 kPa) with a rapid response time of 26 ms, and excellent cycling stability (5600 cycles). The real-time monitoring of human physiological signals such as wrist pulse, voice detection, and finger movements can be achieved by using this MXene–textile sensor. In addition, sensory arrays were successfully applied in the pressure distribution mapping of a key, demonstrating that the pressure sensor can be used as part of wearable devices and human–machine interfaces to sense pressure.